ASSESS_CETA: Assessing the claimed benefits of the EU-Canada Trade Agreement (CETA); CETA: Ökonomische Bewertung der prognostizierten Effekte des EU-Kanada-Freihandelsabkommens - Werner G. Raza; Bernhard Tröster; Rudi von Arnim (Austrian Foundation for Development Research (ÖFSE), 2016)
In late 2016, a decision will be made by the Council of the European Union whether to launch the ratification process of the free trade agreement between the EU and Canada (CETA). The European Commission (EC) is promoting the agreement with the prospects of more trade, stronger economic relations and job creation. However, studies on the economic impact of CETA report only marginal effects on GDP of 0.03% to 0.08% for the whole of the EU. In other words, CETA is expected to generate a one-time income effect of around 20 EUR per EU citizen after a 10 years implementation period. Despite these small effects by CETA, it is worthwhile to question models and assumptions that stand behind these estimations and show neglected risks and adjustment costs. This task is highly relevant, given that the EC is stressing the innovative character of the agreement as it includes intensive regulatory cooperation and strengthens investor protection via the controversially discussed investor arbitration mechanism. CETA is therefore considered the blueprint of the future EU trade policy that focuses on new topics such as regulation, liberalization of public procurement and the promotion and protection of investment. – – Im Herbst 2016 steht auf EU-Ebene die Entscheidung an, ob das ausverhandelte Freihandelsabkommen CETA zwischen der EU und Kanada angenommen wird. Die Europäische Kommission (EK) wirbt für das Abkommen mit der Förderung von Handelsbeziehungen und der Schaffung von Arbeitsplätzen. Jedoch kommen auch die von der EUKommission beauftragten Studien nur zu einer verschwindend geringen Steigerung der Wirtschaftsleistung durch CETA von 0,03% bis 0,08% für die gesamte EU. Dies entspricht nach einer mehrjährigen Implementierungsphase des Abkommens einem einmaligen Einkommensgewinn von 20 Euro pro EU-BürgerIn. Zudem gilt es, die Annahmen und Modelle hinter diesen Ergebnissen zu hinterfragen und die nicht beachteten Risiken und Anpassungskosten offenzulegen. Dies ist umso wichtiger, als nicht zuletzt die EU-Kommission selbst die Neuartigkeit des Abkommens betont, durch das in vielen Bereichen die Zusammenarbeit in Regulierungsfragen intensiviert und der Investorenschutz durch die vieldiskutierte Investor-Staat-Streitbeilegung (Investment Court System, ICS) ausgebaut wird. CETA gilt damit als eine Vorreiterin für die künftige Handelspolitik der EU, in der Themen wie Regulierung, Liberalisierung des öffentlichen Beschaffungswesens und Schutz von Investitionen im Mittelpunkt stehen.
Additional information: Commissioned by the Chamber of Labour Vienna. Updated Final Report, 03 August 2016
Keywords: 330